2021
DOI: 10.3390/cells10051223
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning or Postconditioning with 8-Br-cAMP-AM Protects the Heart against Regional Ischemia and Reperfusion: A Role for Mitochondrial Permeability Transition

Abstract: The cAMP analogue 8-Br-cAMP-AM (8-Br) confers marked protection against global ischaemia/reperfusion of isolated perfused heart. We tested the hypothesis that 8-Br is also protective under clinically relevant conditions (regional ischaemia) when applied either before ischemia or at the beginning of reperfusion, and this effect is associated with the mitochondrial permeability transition pore (MPTP). 8-Br (10 μM) was administered to Langendorff-perfused rat hearts for 5 min either before or at the end of 30 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 78 publications
(91 reference statements)
0
9
0
Order By: Relevance
“…It has been demonstrated that IP limits the infarct size, and attenuates necrosis, apoptosis as well as cardiac dysfunction due to I/R injury [ 98 , 99 , 100 , 101 , 102 , 103 ]. These beneficial effects of IP are reported to be mediated through the activation of adenosine receptors [ 99 ] and protein kinase C activity [ 101 , 104 , 105 , 106 , 107 ], as well as due to reduced phospholipase activities [ 108 ] and the attenuation of TNF-α levels [ 109 ].…”
Section: Subcellular Modification Due To Ischemic Preconditioningmentioning
confidence: 99%
“…It has been demonstrated that IP limits the infarct size, and attenuates necrosis, apoptosis as well as cardiac dysfunction due to I/R injury [ 98 , 99 , 100 , 101 , 102 , 103 ]. These beneficial effects of IP are reported to be mediated through the activation of adenosine receptors [ 99 ] and protein kinase C activity [ 101 , 104 , 105 , 106 , 107 ], as well as due to reduced phospholipase activities [ 108 ] and the attenuation of TNF-α levels [ 109 ].…”
Section: Subcellular Modification Due To Ischemic Preconditioningmentioning
confidence: 99%
“…HK2 is also a well-known regulator of mPTP opening. Accordingly, the cell-permeable cAMP analog 8-Br has recently been shown to protect the heart against regional I/R injury at the onset of reperfusion by promoting the binding of HK2 to mitochondria and inhibiting mPTP, as measured by the reduction in Ca 2+ -induced mitochondria swelling [237]. This study contrasts with the one reported by Pereira et al (2020), in which in vitro dissociation of mt-HK2 from mitochondria has no effect on mPTP opening in postconditioned hearts [120].…”
Section: Pyroptosismentioning
confidence: 99%
“…Acute myocardial infarction remains one of the most significant causes of death and post-event functional disability in population throughout the world [1]. In the circumstances the myocardium is deprived of blood that leads to an acute mass death of its cells and as a consequence results in the loss of cardiac contractility, collagen scar formation and subsequent progressing remodeling as well as heart insufficiency [2].…”
Section: Introductionmentioning
confidence: 99%